Localized Surface Plasmon Enhanced Laser Reduction of Graphene Oxide for Wearable Strain Sensor. Issue 5 (31st March 2021) - Wan, Zhengfen; Wang, Shujun; Haylock, Ben; Wu, Zhiqing; Nguyen, Tuan‐Khoa; Phan, Hoang‐Phuong; Sang, Robert; Nguyen, Nam‐Trung; Thiel, David; Koulakov, Sergio; Trinchi, Adrian; Gao, Yongsheng; et al.
Abstract: Laser reduced graphene has been increasingly attracting broad attention owing to its unique properties and potential applications in energy conversion and storage, flexible electronics, optoelectronics, and nanocomposites. In this study, graphene sheets decorated with Au nanoparticles are fabricated in situ using milliwatt femtosecond laser reduction. The findings reveal an enhancement in both the reduction of graphene oxide sheets and the nucleation and growth of the Au nanoparticles during the in situ laser treatment. Three stages of reactions are considered, namely, (i) the spontaneous redox reaction between HAuCl4 and graphene oxide, (ii) the laser‐induced decomposition of HAuCl4 and reduction of graphene oxide, and (iii) the localized surface plasmon resonance enhanced photoreduction in the presence of Au particles. Moreover, the Au nanoparticles form densely and evenly distributed square‐lattice‐like microcrack networks that ensure a linear resistance change over the tested strain range. This microcrack network architecture enables the development of flexible graphene/Au strain sensors with gauge factors up to 52.5, and linear behaviour up to 25.4% strain. This strain sensor is demonstrated to effectively monitor human motions. The findings leverage the resistive properties of graphene/metal nanoparticle composites with fundamental mechanisms, laying a critical step toward highly functional, low‐cost, flexible, and wearable graphene‐based electronics. Abstract : Graphene sheets decorated with Au nanoparticles are fabricated by laser reduction. Enhancement in both the reduction of graphene oxide and the in situ formation of the Au nanoparticles is found. The graphene/Au is applied for the flexible strain sensor, which shows a gauge factor of 52.5 and a single linearity up to more than 25.4% strain.